Diary of a wimpy kid : double down - Kinney, Jeff (New York : Amulet Books, 2016)
Greg Heffley's mom wants him to take a break from video games while Halloween approaches and he comes up with an idea to make a movie.
1010L
Accelerated Reader AR
Accelerated Reader
Reading Counts RC
Accelerated Reader AR; MG; 5.5; 3.0.; Accelerated Reader; 5.5.; Reading Counts RC; 8.4; 6.0; 69876.
AR
Keywords: Halloween -- Juvenile fiction; Video games -- Juvenile fiction; Families -- Juvenile fiction; Diaries -- Juvenile fiction; Motion pictures -- Production and direction -- Juvenile fiction; Humorous stories